The reality of digital transformation governance and the obstacles to its application at Princess Noura bint Abdel Rahman University from the point of view of academic leaders in the faculties of education, administration and business - Alhazmi, Ohoud Talal (Journal of Educational and Psychological Sciences, 2023)
This study aimed at recognize the reality of governance and its role in digital transformation and the obstacles to its application at Princess Noura bint Abdel Rahman University. In order to achieve the research's objectives, the survey analytical descriptive curriculum was used. The search tool was an identification, which was distributed to all commanders. The Faculty of Education, Business and Administration at Princess Noura bint Abdul Rahman University in Riyadh City elected 23 women leaders during the academic year 1443 AH/2023. One of the most notable findings is the general calculation of the views of the study sample of academic leaders on the reality of digital transformation governance (Policies and Procedures- Technical- Organizational Effectiveness) at Princess Noura bint Abdel Rahman University averaging an average of (3.74 of 5.00) which belong to Category IV of the PentaC scale is the signal category (Average), of the most important results is the absence of statistically significant differences at the indicative level (0.05) between the averages of the study’s estimates of the reality of the numerical sequence of the variables (academic qualifications, administrative positions). It also indicated that there are statistically significant differences at the significance level (0.05) between the averages of the technical study’s assessments of the reality of digital transformation due to the variable (years of service). He has been in contact with them for over 10 years. the researcher has recommended give more powers to leaders to activate governance and digital transformation, and develop governance systems to keep pace with the continuous modernization of digital transformation.
Keywords: Governance and its constraints; Digital transformation; Academic Leaders' Perspective